2006
DOI: 10.1002/ajp.20210
|View full text |Cite
|
Sign up to set email alerts
|

Habitat‐specific ranging patterns of Dian's tarsiers (Tarsius dianae) as revealed by radiotracking

Abstract: Dian's tarsier Tarsius dianae, one of the smallest primates on earth, is endemic to the central regions of Sulawesi, Indonesia. To evaluate the effects of increasing land use by humans on the ranging patterns of this nocturnal insect hunter, four study plots along a gradient of anthropogenic disturbance were selected for this study. In these plots, 71 tarsiers were captured with mist nets, and 30 of these were fitted with 3.9 g radiotransmitters and subsequently tracked over the course of 2 weeks per animal. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…We captured 2 males with T. lariang-typic genetic signatures several hundred meters outside of their species' usual range. This observation falls into a radius that tarsiers easily cover within a single night (42,47). Although these 2 individuals might also have been translocated and released pets, the steep gradients in allele frequencies at the species boundary and the consistent lack of alien genes in the reference populations suggest that accidental introductions do not play an important role in shaping the genetic structure of tarsier populations in a human-altered landscape.…”
Section: Discussionmentioning
confidence: 79%
“…We captured 2 males with T. lariang-typic genetic signatures several hundred meters outside of their species' usual range. This observation falls into a radius that tarsiers easily cover within a single night (42,47). Although these 2 individuals might also have been translocated and released pets, the steep gradients in allele frequencies at the species boundary and the consistent lack of alien genes in the reference populations suggest that accidental introductions do not play an important role in shaping the genetic structure of tarsier populations in a human-altered landscape.…”
Section: Discussionmentioning
confidence: 79%
“…Group sizes of T. dentatus range from 2 to 7 individuals (Merker 1999(Merker , 2003(Merker , 2006Merker et al 2004Merker et al , 2005 and are thus similar in size and composition to groups of northern Sulawesi's spectral tarsier (e.g., MacKinnon and MacKinnon 1980;Nietsch 1993;Gursky 1995Gursky , 2000Gursky , 2007. Almost always, groups were found to comprise one adult male, between one and three adult females, and their offspring.…”
Section: Group Compositionmentioning
confidence: 98%
“…Activity patterns of the wild T. syrichta revealed by Neri-Arboleda et al [2002] showed that both sexes were most active in hourly distance travelled in the first hour after dusk. The early activity peak for the wild tarsiers is explainable by their being quickly able to reach beneficial hunting grounds [Merker, 2006]. With regard to the peak at the end of the night, Crompton and Andau [1987] and Merker [2006] suggested that since the foraging areas were far away from the sleeping sites, travelling back increased the frequency of this activity.…”
Section: Activity Patterns Of Tarsius Syrichtamentioning
confidence: 99%
“…During the mating season, the tarsiers spent significantly more time travelling at the end of the night. Studies conducted on the wild T. bancanus [Crompton and Andau, 1987] and T. dianae (= dentatus) [Merker, 2006] revealed two peaks for locomotor activity and distance travelled: the first shortly after dusk, and the second before going to sleep at dawn. A twopeak activity rhythm was also described by Nietsch [cited in Merker, 2006] for the wild T. spectrum.…”
Section: Activity Patterns Of Tarsius Syrichtamentioning
confidence: 99%
See 1 more Smart Citation